1619 Paediatric Painful Sickle Cell Crises: A Prospective Audit of Analgesic Practise in a Tertiary Paediatric Emergency Department. (October 2012) - Barrett, MJ; McCoy, S; Cronin, J; Murphy, A; Wakai, A; Geoghegan, R; McMahon, C; Walsh, S; O'sullivan, R
Abstract : Introduction: Although children with painful sickle cell crises (PSCC) frequently present to the Emergency Department (ED), pain in sickle cell disease is often under-recognised, under-treated and treatment may be delayed. We aimed to evaluate pain assessment and management in children presenting to the ED with PSCC. Methods: A 12-month prospective descriptive study of acute pain management of PSCC at an urban tertiary paediatric ED. Pain was assessed by the triage nurse or physician using a validated age appropriate pain scale (Faces, Legs, Activity, Cry, Consolability (FLACC) Scale; Manchester Pain Ruler). Results: There were 96 presentations in 66 patients with PSCC (Table 1 ). Nineteen (19.7%) patients recieved no pre-hospital analgesia. Conclusion: PSCC pain is under-treated, under-monitored and adequate treatment of pain is delayed in our ED. Patients with severe pain appear at highest risk for treatment guideline violation. This is predominantly related to lack of opiate administration. An educational intervention, with/without the inclusion of an easily administered, fast-onset and short-acting opiate e.g. intranasal fentanyl, may decrease the time from ED arrival to effective pain relief.